Carcinoembryonic Antigen in Management of Colorectal Carcinoma. Issue 5938 (26th October 1974) - Booth, S. N.; Jamieson, G. C.; King, J. P. G.; Leonard, J.; Oates, G. D.; Dykes, P. W.
Abstract : Carcinoembryonic antigen (C.E.A.) estimation has been used in the preoperative assessment of colorectal carcinoma patients and has been shown to give a useful guide to the presence of metastatic disease and ultimately to a poor prognosis if the serum concentration is 100 ng/ml or more. C.E.A. has been shown to be a more reliable index of tumour spread than either clinical examination or serum alkaline phosphatase estimation. Raised C.E.A. levels of less than 100 ng/ml do not, however, necessarily imply a poor prognosis. Routine C.E.A. estimation may have a valuable role in the assessment of the colorectal cancer patient by identifying those likely to benefit from postoperative chemotherapy. The test has also been assessed in a group of patients attending cancer follow-up clinics after radical resection of a colorectal tumour. Raised C.E.A. occurred in most of those developing recurrent disease, and in several patients a rising C.E.A. level preceded clinical or biochemical evidence of recurrence. C.E.A. estimation is a superior guide and of clinical importance when applied to the follow-up of the colorectal cancer patient.